UJI BAKTERIOLOGIS BAWANG PUTIH GILING (Allium sativum L.) DARI BEBERAPA PASAR TRADISIONAL DI KOTA PADANG - Putri, Pujiana Okta; Fifendy, Mades; Periadnadi, Periadnadi (STKIP PGRI Sumbar, 2013)
AbstractAt the time the problem of very attractive food security of attention of related people whoand society in the round of food. Garlic as flavor used almost in each; every cookery and food in Indonesia, yielding to feel and typical aroma. Garlic mill have come to materials ready to become which enthused many by society. This research, aim to test bacteriologies at garlic mill (Alium Sativum L.) from some traditional market in the round of the Padang city, which have been conducted in June 2013 in Microbiological Laboratory of Biological Majors, University of Andalas Padang. This Research is conducted with descriptive method, intake of sample conducted by purposive sampling which is each of sample taken by two sample at 5 traditional market in at the Padang that is, Bandar Buat Market, Gaung Market, Lubuk Buaya Market, Pasar Simpang Aru, and market of Siteba. the next conducted by examination of bacteriologies by using method of MPN ( Most Probable Number) by using stages; steps 1. Test anticipation (test presumtive 2. coherent test (test confirmed 3. test completion (test completed) using method of MPN (Most Probable Number) by using combination 5:1:1. From research got by result of all of garlic sample mill to containbacterium with amount of gyration 39 x 107 cell / ml - 143x 107 cell / ml. Garlic Sample mill from five traditional market at Padang Town have gyration assess MPN bacterium of koliform 2,2 - 240 cell / 100 sample ml and bacterium E. coli 0 - 4 cell/ 100 sample ml. The conclude that garlic mill which is sold from some traditional market in at Padang City generally is improper consumed bybecause containing bacterium E. coli > 3 colony / g bacterium and g of koliform > 100 colony / g.